Hallucinations in adolescents and risk for mental disorders and suicidal behaviour in adulthood: Prospective evidence from the MUSP birth cohort study - Connell, M.; Betts, K.; McGrath, J.; Alati, Rosa; Najman, J.; Clavarino, A.; Mamun, A.; Williams, G.; Scott, J. (2016)
© 2016 Elsevier B.V. Background Hallucinations, once equated with serious mental disorders, are common in adolescents. Given the high prevalence of hallucinations, it is important to determine if they are associated with adverse mental health outcomes in adulthood. This study compared the mental health outcomes of participants (aged 30–33 years) in the Mater-University of Queensland Study of Pregnancy (MUSP) who reported hallucinations at (a) 14 years only and (b) 14 and 21 years versus cohort members without hallucinations. Method Participants (n = 333) were aged between 30 and 33 years and (a) reported hallucinations on the Youth Self-Report Questionnaire at 14 and/or the Young Adult Self-Report Questionnaire at 21 years and (b) controls (n = 321) who did not report hallucinations. Lifetime diagnoses of mental disorders were ascertained by the Structured Clinical Interview for DSM Disorders (DSM IV-TR) administered by clinical psychologists. Suicidal behaviour was measured by self report. Results Hallucinations at 14 years only were not associated with an increased risk of mental disorders in adulthood. Hallucinations reported at both 14 and 21 years were associated with lifetime diagnoses of psychotic disorders (OR, 8.84; 95% CI: 1.61–48.43 and substance use disorders (OR, 2.34; 95% CI: 1.36–4.07) and also strongly associated with lifetime suicide attempts (OR, 7.11; 95% CI: 2.68–18.83). Conclusions Most adolescents who experience hallucinations do not have an increased rate of mental disorder in adulthood; however, those with hallucinations that are experienced at more than one point in time are at increased risk of suicidal behaviour and both psychotic and non-psychotic psychopathology.